2019
DOI: 10.1186/s40248-019-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk factors associated with respiratory symptoms among tannery workers in Mojo town, Southeast Ethiopia, 2018: a comparative cross-sectional study

Abstract: Introduction Work-related respiratory diseases (WRDs) account for 10–20% of all chronic respiratory illnesses affecting hundreds of millions of people of all ages. Tannery industries are often associated with hazardous working conditions favourable for respiratory conditions. However, information about the prevalence and occupational factors that predispose to respiratory symptoms is meagre in Ethiopia. This study aimed to investigate the magnitude and risk factors associated with work-related res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Ten primary studies 16,17,[24][25][26][27][28][29][30][31] with 3441 study participants (male = 1983, female = 1458, age range: 18-68 years) were included for the narrative synthesis and meta-analysis. Three studies were unpublished 24,27,31 and seven studies were published from 2014 to 2019.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten primary studies 16,17,[24][25][26][27][28][29][30][31] with 3441 study participants (male = 1983, female = 1458, age range: 18-68 years) were included for the narrative synthesis and meta-analysis. Three studies were unpublished 24,27,31 and seven studies were published from 2014 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,25,26,[28][29][30] The sample size ranged from 196 24 to 566. 31 Four studies were conducted in Addis Ababa, 17,26,27,31 three studies in Oromia Region, 16,29,30 two studies in Amhara region 25,28 and one study in the Southern Nations, Nationalities, and Peoples (SNNP) region. 24 The risk level of each study was rated, and we found all studies were rated as low risk of bias (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these studies examine the effect of working in specific areas or the types of work in the tannery and the health complaints. However, a cross-sectional study in Southeast Ethiopia reported that the odds of developing respiratory symptoms was 3.37 times higher among tannery workers than unexposed workers (Dalju et al, 2019). A previous study from India also found that lifting 10 to 20 kg or >20 kg was associated with asthma (OR = 2.36 and 2.56) and chronic bronchitis (OR = 2.11 and 1.57) (Öry et al, 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…The major morbid conditions observed in these workers include respiratory and eye diseases, accidents, burns, cuts and wounds, skin infections, animal bites, etc. [25,26].…”
Section: Street Sweepers and Dustmentioning
confidence: 99%